Catalogue of Etruscan objects in World Museum, Liverpool - Turfa, Jean MacIntosh, 1947-; Muskett, G. M. (Georgina M.) (Archaeopress Publishing Ltd, 2017)
A catalogue of one of the finest collections of Etruscan artifacts outside of Italy, that of World Museum, Liverpool. This publication is highly illustrated with over 100 plates in full colour.